Maternal Marijuana Exposure and Birth Weight: An Observational Study Surrounding Recreational Marijuana Legalization - Straub, Heather L.; Mou, Jin; Drennan, Kathryn J.; Pflugeisen, Bethann M. (American Journal of Perinatology, 2019)
Objective This study aimed to study the relationship between prenatal marijuana and infant birth weight using natural cohorts established before, during and after the 20-month lapse between legalization and legal recreational sales in Washington State.Study Design Over 5 years, 5,343 pregnant women with documented urine drug screen (UDS) results delivered at Tacoma General Hospital or Good Samaritan Hospital. Maternal medical data were extracted for three delivery cohorts established based on before (T1), during (T2), and after legalization (T3) of recreational marijuana and legalized availability. Univariate and multivariate models were created to study marijuana exposure on infants' birth weight.Results Marijuana exposure increased the risk of low birth weight (LBW; odds ratio [OR] = 1.42, 95% confidence interval [CI]: 1.01–2.01). This was more pronounced in full-term babies (OR = 1.72, 95% CI: 1.10–2.69), and was independently associated with a higher risk for small for gestational age (SGA; OR = 1.51, 95% CI: 1.49–1.53). The associations between marijuana exposure and SGA were maintained in cohort-specific models (OR = 1.53, 95% CI: 1.01–2.32 for T2, and OR = 1.43, 95% CI: 1.01–2.02 for T3, respectively).Conclusion Marijuana exposure verified by UDS was associated with LBW and SGA. However, recreational marijuana legalization and availability did not have direct impact on newborns' risk of LBW or SGA.
Keywords: maternal marijuana use; birth weight; small for gestational age; low birth weight; marijuana legalization